Increased Biological Activity of Aneurinibacillus migulanus Strains Correlates with the Production of New Gramicidin Secondary Metabolites - Alenezi, Faizah N.; Rekik, Imen; Chenari Bouket, Ali; Luptakova, Lenka; Weitz, Hedda J.; Rateb, Mostafa E.; Jaspars, Marcel; Woodward, Stephen; Belbahri, Lassaad (Frontiers in Microbiology, 2017)
The soil-borne gram-positive bacteria Aneurinibacillus migulanus strain Nagano shows considerable potential as a biocontrol agent against plant diseases. In contrast, A. migulanus NCTC 7096 proved less effective for inhibition of plant pathogens. Nagano strain exerts biocontrol activity against some gram-positive and gram-negative bacteria, fungi and oomycetes through the production of gramicidin S (GS). Apart from the antibiotic effects, GS increases the rate of evaporation from the plant surface, reducing periods of surface wetness and thereby indirectly inhibiting spore germination. To elucidate the molecular basis of differential biocontrol abilities of Nagano and NCTC 7096, we compared GS production and biosurfactant secretion in addition to genome mining of the genomes. Our results proved that: i) Using oil spreading, blood agar lysis, surface tension and tomato leaves wetness assays, Nagano showed increased biosurfactant secretion in comparison with NCTC 7096, ii) Genome mining indicated the presence of GS genes in both Nagano and NCTC 7096 with two amino acid units difference between the strains: T342I and P419S. Using 3D models and the DUET server, T342I and P419S were predicted to decrease the stability of the NCTC 7096 GS synthase, iii) Nagano produced two additional GS-like molecules GS-1155 (molecular weight 1155) and GS-1169 (molecular weight 1169), where one or two ornithine residues replace lysine in the peptide. There was also a negative correlation between surface tension and the quantity of GS-1169 present in Nagano, and iv) the Nagano genome had a full protein network of exopolysaccharide biosynthesis in contrast to NCTC 7096 which lacked the first enzyme of the network. NCTC 7096 is unable to form biofilms as observed for Nagano. Different molecular layers, mainly gramicidin secondary metabolite production, account for differential biocontrol abilities of Nagano and NCTC7096. This work highlighted the basis of differential biological control abilities between strains belonging to the same species and demonstrates techniques useful to the screening of effective biocontrol strains for environmentally friendly secondary metabolites that can be used to manage plant pathogens in the field.